Dental age estimation by assessing the pulp volume of five teeth in a peruvian population using cone beam computed tomography images = Estimación de la edad dental evaluando el volumen pulpar decinco dientes utilizando imágenes de tomografías computarizadas de haz cónico en una población peruan - Salvatierra Gálvez, Juliana Magaly; Díaz Suyo, Antonio; Alvarado Muñoz, Erika Ruth; Kapoor, Priyanka; Chowdhry, Aman (2023)
Dental age estimation is very important for individual identification in criminal and civil forensic investigations. One of the methods for age estimation is studying age related changes in pulp volume of teeth. The objective of the current study was to estimate dental age from the pulp volume of five different categories of teeth of a Peruvian sample using cone beam computed tomography (CBCT). Retrospective CBCT records of 231 patients [females (134), males (97), age: 12-60 years] were included in the study, categorized into five different age groups (12-19, 20-29, 30-39, 40-49, 50-59, 60 years and older). Dental pulp volume of five categories of teeth(upper canines, left upper central incisors, left upper first molars, lower left first premolars, first molars) were analyzed using Romexis® 5.3.3.5 software for each patient. There was a reduction in the pulp volume of upper right and left canine with age. The pulp volume was lowest in people aged 60 years and over. Linear regression analysis of the pulp volume and chronological age showed a coefficient of determination of 30%, suggesting a weak correlation. A weak correlation between dental pulp and age is derived. But, a robust large homogenous sample of teeth in future for different age groups may establish a reliable regression equation.
La estimación de la edad dental en personas vivas y cadáveres es muy importante para la Odontología Forense, sobre todo en casos de identificación en investigaciones legales y sociales. El objetivo del estudio fue estimación de la edad dental mediante la medición del volumen pulpar de imágenes dentales en tomografía computarizada de haz cónico (TCHC) de pacientes peruanos. Fueron analizadas 231 TCHC de pacientes entre 12 a 60 años a más. [Mujeres (134), hombres (97)] se dividieron en seis grupos de edad (12-19, 20-29, 30-39, 40-49, 50-59, 60 años a más). El análisis volumétrico de la pulpa dental se realizó en un total de 1155 dientes (caninos superiores, incisivos centrales superiores izquierdos, primeros molares superiores izquierdos y primeros premolares inferiores izquierdos), mediante el software Romexis® 5.3.3.5. El análisis de regresión lineal mostró un coeficiente de determinación del 30% que sugiere una correlación débil entre la relación del volumen pulpar de los dientes y la edad. El volumen pulpar de los caninos superiores derecho e izquierdo disminuyó a medida que aumentaba la edad y el volumen pulpar en dientes de personas de 60 años a más fue el más bajo. Sin embargo, se pueden proponer estudios futuros para incluir una gran muestra homogénea de dientes en diferentes categorías y grupos de edad para confirmar la correlación y establecer una ecuación de regresión confiable.
En revista Odóvtos, vol. 25, no.3 (septiembre-diciembre 2023)
Descripción basada en el contenido visto el 21 de enero, 2025
También disponible en formato HTML y EPUB